A Study on Semantic Web Mining And Web Crawler (International Journal of Engineering and Computer Science, 2013)
The main purpose of the research is to study and understand the concepts of semantic web mining and web crawlers. Everyday tens to hundreds of millions of web information are generated and they answer tens of millions of queries. The most important thing is search engine to search the performance, quality of the results and ability to crawl, and index the web efficiently. The primary goal is to provide high quality search results over a rapidly growing World Wide Web in semantic web mining and to download the information from web crawling is needed. This research work aimed at how the information’s are extracted from the web using crawler method and studying the research areas of semantic web mining.